Policarpo e Ireneo nel frammento a Florino, CPG 1308 (Apud Eusebio, HE 5,20,4-8) - Navascués, Patricio de (Augustinianum, 2014)
This passage from Irenaeus’ Letter to Florinus (cf. Eus. Caes., HE 5, 20, 4-8) offers sufficient material for reflection on the patristic function within dogmatic theology, provided that we understand both Polycarp in the role of a Church Father standing in direct contact with the apostolic kerygma, and, at times, Irenaeus as a theologian reflecting on faith. We begin with the apostolic kerygma which Policarp first hears, learns and sets down clearly, then later recalls and transmits in harmony with faith and scripture. Irenaeus, for his part, carries out the role of theologian to the extent to which he listens to what was handed on attentively, commits it to memory, reflects upon it and then witnesses to it, moved by the grace of God. The language utilized by Irenaeus reveals reminiscences of the Platonic tradition, apropos of the function of memory and scripture (cf. Phaedrus) and of the Philonian tradition, apropos of the theological content of the biblical term to ruminate. The analysis undertaken offers a ground upon which to think about new relationships between dogmatic and patristic theologies, a question that can be developed in a later article.